The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1021/acsnano.5b06066
|View full text |Cite
|
Sign up to set email alerts
|

Mussel-Inspired Anchoring of Polymer Loops That Provide Superior Surface Lubrication and Antifouling Properties

Abstract: We describe robustly anchored triblock copolymers that adopt loop conformations on surfaces and endow them with unprecedented lubricating and antifouling properties. The triblocks have two end blocks with catechol-anchoring groups and a looping poly(ethylene oxide) (PEO) midblock. The loops mediate strong steric repulsion between two mica surfaces. When sheared at constant speeds of ~2.5 μm/s, the surfaces exhibit an extremely low friction coefficient of ~0.002–0.004 without any signs of damage up to pressures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
121
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(128 citation statements)
references
References 39 publications
5
121
2
Order By: Relevance
“…40 To further increase the attachment strength catechol anchoring groups on both ends of a poly(ethylene oxide) chain have recently been used to build a layer with predominantly loop structures. 41 Very low friction forces and no erosion were observed in these experiments, and this was related to low interpenetration of loops and strong surface anchoring, respectively. Considering the discussion above one can predict that lubricants that are used for achieving low friction forces in aqueous media should be highly hydrated and strongly attached to the substrate surface, and that the surface should be fully covered by the lubricant.…”
Section: Lateral Motion Of Molecules Along the Surfacementioning
confidence: 61%
“…40 To further increase the attachment strength catechol anchoring groups on both ends of a poly(ethylene oxide) chain have recently been used to build a layer with predominantly loop structures. 41 Very low friction forces and no erosion were observed in these experiments, and this was related to low interpenetration of loops and strong surface anchoring, respectively. Considering the discussion above one can predict that lubricants that are used for achieving low friction forces in aqueous media should be highly hydrated and strongly attached to the substrate surface, and that the surface should be fully covered by the lubricant.…”
Section: Lateral Motion Of Molecules Along the Surfacementioning
confidence: 61%
“…This transition is more sterically and entropically demanding compared to the compression of linear grafts, which are characterized by a higher degree of freedom. Remarkably, the higher resistance towards external compression by loop brushes translated into an excellent biopassivity (protein repellent behaviour), as it was demonstrated for loop PEG brushes featuring different anchoring groups . In addition, Zeng and co‐workers demonstrated how the physicochemical and morphological properties of surface‐grafted loops could substantially improve the biopassivity of PEG brushes against the adsorption of bovine serum albumin (BSA), the most abundant serum protein (Figure ) …”
Section: Loop Brushesmentioning
confidence: 89%
“…Hydrophilic loop brushes were also fabricated, especially concentrating on PEG and polyzwitterionic (PZW) assemblies. In the first case, multi‐catechol‐based segments ensured the formation of loop brushes on SiO 2 and mica (Figure ), while multiblock copolymers including a loop‐forming, central block of PZW molecular brushes were assembled on negatively charged mica surfaces by means of quaternized poly‐2‐(dimethylaminoethyl)methacrylate (qPDMAEMA) side‐blocks (Figure ) …”
Section: Loop Brushesmentioning
confidence: 99%
“…Specifically, the tribological properties of conventional bulk plastics [35][36][37][38], rubber-like materials [39], fiber-reinforced composites [40], polymer nanocomposites [41][42][43], cross-linked hydrogels [44], end-grafted polymers (a.k.a. polymer brushes) [45], mammalian articular joints [46], gecko-inspired surfaces [47], and mussel-inspired coatings [48] have been investigated. For viscoelastic solids, such as polymers, it has been shown that friction is velocity-dependent and Equation (1) cannot be valid over a wide range of sliding velocities.…”
Section: Friction Laws For Viscoelastic Solidsmentioning
confidence: 99%